Settlement of indonesian human rights violations in the past through restorative justice approaches - Rosnida Rosnida (Jurnal Hukum Volkgeist, 2020)
This paper aimed to identify and analyze the resolution of past gross human rights violations in Indonesia through a restorative justice approach. The type of research used is normative legal research, using a juridical approach, the type of data used is secondary data consisting of primary legal materials, secondary legal materials, tertiary legal materials, data analysis used is qualitative analysis. Based on the results of the research, it is concluded that so far the Attorney General has not been proactive in looking for various legal facts that can support the evidence previously presented by Komnas HAM. The Attorney General in cases of gross human rights violations tends to be passive, even though the law instructs him to carry out an investigation as soon as possible after he receives a file from Komnas HAM. So far, Komnas HAM has completed the investigation results files and submitted them to the Attorney General to be followed up in the investigation process. However, the current problem is that the Attorney General's authority in conducting investigations has never been optimal, because it is influenced by various factors, the role of legal instruments; laws and regulations with human resources capacity as well as supporting facilities and facilities, unable to resolve past cases of gross human rights violations, the restorative justice approach is a paradigm that can be used as a framework for resolving cases of past gross human rights violations that aim to address dissatisfaction with the operation of the current human rights justice system.